Fabrication and Characterization of Drug-Loaded Conductive Poly(glycerol sebacate)/Nanoparticle-Based Composite Patch for Myocardial Infarction Applications - Zanjanizadeh Ezazi N.; Ajdary R.; Correia A.; Mäkilä E.; Salonen J.; Kemell M.; Hirvonen J.; Rojas O.J.; Ruskoaho H.J.; Santos H.A. (American Chemical Society, 2022)
Heart tissue engineering is critical in the treatment of myocardial infarction, which may benefit from drug-releasing smart materials. In this study, we load a small molecule (3i-1000) in new biodegradable and conductive patches for application in infarcted myocardium. The composite patches consist of a biocompatible elastomer, poly(glycerol sebacate) (PGS), coupled with collagen type I, used to promote cell attachment. In addition, polypyrrole is incorporated because of its electrical conductivity and to induce cell signaling. Results from the in vitro experiments indicate a high density of cardiac myoblast cells attached on the patches, which stay viable for at least 1 month. The degradation of the patches does not show any cytotoxic effect, while 3i-1000 delivery induces cell proliferation. Conductive patches show high blood wettability and drug release, correlating with the rate of degradation of the PGS matrix. Together with the electrical conductivity and elongation characteristics, the developed biomaterial fits the mechanical, conductive, and biological demands required for cardiac treatment.